FACTORS TO CERTIFIED FOOD CONSUMPTION IN BRAZIL - Valent, Joice Zagna; Vieira, Tatiana Regina; Bruzza, Adriano; Rodrigues, Renata Gonçalves; Celia, Andrea Polidori; Schmidt, Verônica (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Agri-food products diversity and contemporary problems of food safety are leading to an uncertainty about the quality of products along the production chain. In this regard, the present study aimed to identify main factors in decision making of certified products consumers. To this effect, was performed a non-probabilistic sampling survey by sending an online questionnaire answered by 220 people. Among the factors that determine certified products consumption are monthly income, educational level and number of people in the family. The high price is considered as one of the barriers to certified products consumption. It was found that there are consumers who do not know what certification is. This fact constitutes an obstacle on certified products buying decision. Studies show an increase in importance when consumers attach to certification after educational campaigns. In this sense, it is necessary to develop information and awareness campaigns of the characteristics of certified products.